2018
DOI: 10.1177/2324709618812196
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Macrophage Activation Syndrome Presenting as the First Manifestation of Systemic Lupus Erythematosus

Abstract: Macrophage activation syndrome (MAS) itself is a rare, potentially life-threatening complication of a rheumatic disease, mostly seen in juvenile idiopathic arthritis. It infrequently occurs in systemic lupus erythematosus (SLE), and it is extremely rare to be the first presentation of SLE. In a study of 511 patients with SLE, 7 cases (1.4%) of MAS were identified. In all the cases, MAS was simultaneous to the presentation of SLE in this article, we report a case of a patient with MAS who presented with fever, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Studies have stated that macrophage activation syndrome (MAS) is more prevalent in patients with Juvenile SLE [ 30 ]. MAS is characterized by high fever, hepatosplenomegaly, hepatic dysfunction, pancytopenia, and clotting disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have stated that macrophage activation syndrome (MAS) is more prevalent in patients with Juvenile SLE [ 30 ]. MAS is characterized by high fever, hepatosplenomegaly, hepatic dysfunction, pancytopenia, and clotting disorder.…”
Section: Discussionmentioning
confidence: 99%
“…[5] The Hscore in the patient presented here was 299, which exceeded the diagnostic cutoff of 169 (Table 2). Poudel et al [6] reported a patient who presented with MAS as the initial manifestation of SLE, and concluded that early diagnosis is crucial because mortality is high in untreated cases.…”
Section: Discussionmentioning
confidence: 99%
“…This reciprocal interaction between the initiating factors (IFNs, autoantibodies, immune complexes, infectious insult, or injury) and downstream responses (complement activation, neutrophil accumulation, and activation) likely plays an essential role in driving SLE-associated lung involvement [49]. Macrophage activation syndrome (MAS) has been described in several case reports of patients with lupus; however, its relationship is unclear and is rarely the first presentation of SLE [53][54][55]. In juvenile SLE, some cases of MAS that developed in the initial stage should be treated with immunosuppressants [56].…”
Section: Pathogenesismentioning
confidence: 99%